THE MYTH IN THE FANTASTIC (on the material of M. and S. Diachenky’s novel “Wild energy. Lana”) - Khorob, S. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The genre variety of the novel – the novel-rhythm, “is working” on the conception of the work starting from the title through the central imagecharacter of Lana and other personages and finishing by the mythological background of the heroes, symbols, details.